The exiled king - Remy, Sarah (Remy, Sarah. Bone magic, 2017)
"Avani and Mal's journey comes to its gripping conclusion. The desert has outgrown its boundaries ... The warriors of the sands have united for the first time. They are newly privy to the secret sidhe roads beneath mountains, the ones that used to keep the flatlands safe. And they are marching toward Wilhaiim with weapons of steel. Wilhaiim is out of options ... King Renault's choice is untenable: watch the flatlands fall, or work with Malachi Doyle in a secret gambit to revive Wilhaiim's ancient mechanized guardians, the Automata. The Automata have a terrible, bloodied history, but Mal believes they are his kingdom's only hope of survival. Mal wavers on the edge of insanity ... Avani lives with Mal in her head, an unwilling witness to his increasing madness. Her nights are filled with dreams of darkness and despair, her days troubled by guilt and uncertainty. Her beloved Goddess draws distant as Mal's influence takes its toll. And as the bloodshed, brutality, and loss multiples, she and Mal will learn that determination is sometimes more potent than sorcery ... and that the greatest sacrifices are often inescapable."--Publisher.